Leitura na educação de jovens e adultos: f(r)estas à práxis interlocutiva para um bem viver - Souza, Almeri Freitas de (2014)
This thesis is based on theoretical research into the phenomenon of reading in Youth and Adult Education (YAE), in which we seek to answer two questions: what epistemological elements should be fundamental for the teaching of reading in YAE? What are we (re) learning through and about the practice of reading in YAE with a view to good living ? We believe that these answers could provide important elements for a praxis of reading in YAE which guarantees a widening of the possibilities for social participation by the subjects of the educational process, in a way which makes the process of learning to read less opaque, with the indication of possible and adequate paths for the recreation of this activity in YAE. Such paths, based on the perspective of Popular Education and as such with respect for the different social subjects, in the cultivation of lifelong learning and in the most diverse learning communities, without losing good living from sight which implies a good living together , that is, the construction of ethical, democratic, symbiotic, balanced and harmonious (inter)relations between persons and between them and nature all, without a sense of inferiority or superiority, and conceived as interrelated and interdependent elements which make up the cosmos. Amongst the areas selected for this study, we can list the contributions of the Historical-cultural Theory of Human Psyche (Vygotsky), of Pedagogy (in particular, the Freirean postulates), of Philosophy (Dialectics and Historical Materialism), of Social Semiotics and some of the strands of contemporary Linguistics, such as Socio-linguistics, and Textual Linguistics, Discourse Analysis, Pragmatics and bakhtinian studies (interactionism). In our search for coherence with the principles of Popular Education, a qualitative research methodology was chosen and, on the basis of that, we opted for a diversification of ideas and contexts. In this way, the process of content analysis in which is implicit the discursive character of each and every enunciation, made use of educational theories and proposals and extant practices (already systematized and registered) as well as data resulting from experiences in which the researcher in her condition as educator in YAE was involved. We sought in this way to establish new working hypotheses, with the results obtained being reflected again in and for YAE, considered as a process of lifelong learning (human right) and a possible and necessary locus for popular education. In accordance with the results of this research, reading in YAE as interlocutive praxis constitutes a pedagogical process which makes possible the enlargement of the construction of knowledge and transformative practices in the search for good living which corroborates the initial thesis of this research. The right to the will to produce truth is still an unequal, tense and conflictive battle, although simultaneously pregnant with contradictions which can even be transformed into gaps housing new positions with regard to the world, in new humanizing potentializing conquests of good living for young people, adults and the elderly who, as historical subjects, can be conditioned but not determined and, therefore, can be re-dignified as subjects of rights, as constructors of new rights, personally and collectively, in and through interlocutive praxis.